Coal-based carbon anodes for high-performance potassium-ion batteries. (June 2019) - Xiao, Nan; Zhang, Xiaoyu; Liu, Chang; Wang, Yuwei; Li, Hongqiang; Qiu, Jieshan
Abstract: Potassium-ion batteries (PIBs) are considered as a viable alternative to lithium-ion batteries in large scale stationary energy storage. However, the low cost, high rate and long life anode still remains great challenge for the commercialization of PIBs. Herein, high performance carbon anodes for PIBs have been successfully prepared from low-cost and abundant coal through ball-milling, acid washing, oxidation and carbonization. We discover that the potassium storage performances of coal-based carbons are closely related to the coal rank. A middle-rank bituminous coal-based carbon anode delivers a high reversible capacity of 260 mAh g −1 at 0.05 A g −1 and maintains 118 mAh g −1 after 1200 cycles at 1 A g −1 . Moreover, at higher current densities of 0.1, 0.5, and 5.0 A g −1, it maintains high storage capacities of 230, 176, and 88 mA h g −1, respectively. The low cost and high performance coal-based carbon anodes are supposed to accelerate the development of PIBs toward future large-scale applications. Graphical abstract: The relatively ordered carbon clusters with enlarged interlayer spacing of B1 -A-900 can improve its K + diffusion coefficient, contributing to an excellent rate performance. Image 1